2010
DOI: 10.1007/s12105-010-0222-2
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Adenocarcinoma of the Colon: Early Manifestation in Gingival Tissue

Abstract: A case of gingival metastasis of adenocarcinoma of the colon is reported, the lesion being an early clinical indication of a primary malignant tumor. The diagnosis of metastatic lesion in the oral region is always challenging, both to clinician and to the pathologist, due to its rarity and complexity. In the present case, the clinical hypothesis was peripheral ossifying fibroma or pyogenic granuloma. Histologically, the biopsy tissue revealed a malignant neoplasm not connected to the mucosal surface. Immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…To better understand the association between oral cavity metastases and colon cancer, 12 cases of oral cavity metastases of colon cancer, including the present case, were reviewed [6,7,[10][11][12][13][14][15][16][17][18]; Table I]. It was observed that mandibular metastases from colon cancer regularly occurred the sixth and seventh decades of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the association between oral cavity metastases and colon cancer, 12 cases of oral cavity metastases of colon cancer, including the present case, were reviewed [6,7,[10][11][12][13][14][15][16][17][18]; Table I]. It was observed that mandibular metastases from colon cancer regularly occurred the sixth and seventh decades of life.…”
Section: Discussionmentioning
confidence: 99%
“…Although liver metastases from colon cancer has a relatively favorable prognosis (progression-free survival of ~23 months), metastases from colon cancer remain to be further investigated (4,5). Moreover, colon cancer metastases to rare sites, such as the oral cavity, carry a worse prognosis (6).…”
Section: Introductionmentioning
confidence: 99%
“…One important aspect of the biology of cancer is the development of metastases and their diagnosis is always challenging for both clinician and the pathologist, due to its rarity and complexity (Servato et al, 2013;Soares et al, 2011). Kwon et al (2006), proposed some criteria for metastatic tumor diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The metastatic rate in the posterior body of the mandible is higher than that in the symphyseal region [ 5 ]. The gingivae (55 %) followed by the tongue (30 %) are the most common soft tissue sites affected by metastatic malignancy [ 4 ]. In the present case, the metastatic lesion has been presumed to develop in the gingival tissue of the symphysis.…”
Section: Case Presentationmentioning
confidence: 99%
“…In the oral cavity, hard tissues such as the jawbone are more commonly affected than soft tissues such as the gingiva [ 3 ]. The gingivae (55 %) followed by the tongue (30 %) are the most common soft tissue sites affected by metastatic tumor [ 4 ]. Colonic carcinoma is one of the most common malignant neoplasms worldwide.…”
Section: Introductionmentioning
confidence: 99%